Hybrid process of low temperature nitriding-carburizing for austenitic stainless steel - Triwiyanto, Askar (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Austenitic stainless steels are the most widely used in the chemical and petrochemical industry, cryogenic vessels, heat exchangers, machinery for paper, pulp, textile, pharmaceutical, and domestic equipment. This type of steels has excellent corrosion resistance and forming characteristics. However, due to its inherent austenitic structure this material has relatively low hardness as well as poor wear resistance. Earlier attempts to increase the surface hardness and wear resistance of austenitic stainless steels by surface treatments, such as conventional nitriding and nitrocarburizing, led to the deterioration in corrosion resistance arising from the depletion in chromium in the hardened layer. Attempts have been made to harden the surface of these materials without compromising their good corrosion resistance. These led to the development of low temperature nitriding and carburizing processes which are carried out at temperatures lower than 500 °C. So far, low temperature nitriding and caruburising of austenitic stainless steels have been successfully conducted by innovative techniques, including plasma nitriding, ion beam nitriding and ion implantation. However, no attempts have been made to harden these materials commercially using conventional processes such as gaseous and fluidized bed processes. This work describes the results of diferent thermochemical treatments of austenitic stainless steels carried out at 450 oC and 470 oC in a fluidised bed furnace which nitriding, carburizing and the newly developed hybrid process involving the simultaneous and sequential incorporation of nitrogen and carbon to form a dual layer structure. All these treatments formed alloyed layers with a common feature of being precipitation-free and supersaturated with nitrogen, or carbon or both in the austenite lattice which is known as S-Phase or expanded austenite. However the layer thickness was not uniform in any of these treatments and an effective layer was produced after 8h treatment duration. The nitriding treatment produced thicker and harder layer compared to other treatments; the maximum hardness was over 1500 Hv for nitriding and it was 500 Hv for carburizing treatment. The nitriding treatment sample showed better wear properties due to higher hardness value. The hybrid process of this thermochemical treatment at 470 oC showed superior thickness of 8.4 @m to 12.2 @m expanded austenite layer compared to another treatments at 450 oC without the presence of nitride particles